Analysis of the effect of hoax news development in Indonesia using structural equation modeling-partial least square / Christopher Andreas ... [et al.] - Andreas, Christopher; Priandi, Sakinah; Bonar Simamora, Antonio Nikolas Manuel; Mardianto, M. Fariz Fadillah (2021)
Freedom of the press as one of the pillars of the Sustainable Development Goals (SDGs) has made information dissemination more widespread. However, this freedom is followed by the development of hoax news that continues to grow in Indonesia. For this reason, a study was conducted to analyze the factors that significantly influence the development of hoax news in Indonesia. In this case, the exogenous variables used are internal factors, external factors, media credibility, and government regulations. The endogenous variables used are the development of hoax news in mass media and social media. By applying the Structural Equation Modeling-Partial Least Square (SEM-PLS) method, it is found that internal factors and government regulations have a significant influence on the development of hoax news on social media. Through this research, policy recommendations related to internal factors and government regulations can be formulated so that the development of hoax news can be minimized.